Survey, symptomatology and detection of an isolate of maize stripe virus on sorghum in Karnataka - V. MUNIYAPPA, Y.D. NARAYANA and (Indian Phytopathology, 2002)
Sorghum stripe disease (SStD), caused by an isolate of maize stripe virus on sorghum (MStV-Sorg), was observed during a field survey, carried out in sorghum growing areas of Karnataka during 1991-92, and its incidence ranged from 0-13.5%. The disease is characterized by continuous chlorotic stripe and bands on leaves and affected plants were dwarfed and produced poor panicles with few grains. Of the 276 field samples collected from 33 locations, 197 reacted positive in ELISA test. In nature, the disease is transmitted by a delphacid plant hopper (Peregrinus maidis) and its population ranging from 1 to 6 per plant was observed during the survey. The minimum acquisition access period (AAP) and inoculation access period (IAP) was found to be 4 and 1 h respectively. The rate of transmission was 42%, when single viruliferous P. maidis was used for inoculation of seedling. Of the several cultivated fodder and weed hosts tested under artificial inoculation, other than sorghum, only wheat (Triticum aestivum) and Johnson grass (Sorghum halepense), a perennial fodder grass, showed characteristic symptoms similar to that on sorghum and reacted positively in ELISA test.